2010
DOI: 10.1063/1.3483929
|View full text |Cite
|
Sign up to set email alerts
|

Probing of interfacial charging and discharging in double-layer devices with a polyimide blocking layer by time-resolved optical second harmonic generation

Abstract: By using time-resolved electric field induced second harmonic generation, we directly probed interfacial charging and discharging in double-layer devices with an indium tin oxide (ITO)/polyimide(PI)/N,N′-di-[(1-naphthyl)-N,N′-diphenyl]-(1,1′-biphenyl)-4,4′-diamine (α-NPD) (or pentacene)/Au structure, where PI serves as a blocking layer. The results showed that carriers injected from Au electrodes were responsible for interfacial charging and discharging, but different carrier behaviors were observed for pentac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Upon application of the external voltage, SH intensity increases from baseline level (at V ex = 0) until it reaches its maximum value at around 10 À7 s, the increase corresponding to charging of electrodes. The response time of the charging process agrees well with the calculated value for the equivalent circuit, s RC = R s C⁄ % 4 Â 10 À8 s. Smooth carrier injection follows, with holes being transported and accumulated at the pentacene/polyterpenol interface, as reflected by the rapid decrease in SH intensity commencing at $5 Â 10 À6 s to its initial baseline level, which it reaches at approximately 10 À5 s. Similar carrier injection behaviour has been reported for comparable pentacene-based device with polyimide blocking layer, where SH intensity was demonstrated to relax to the zero level at approximately 10 À3 s under forward bias charging conditions [36]. According to the equivalent circuit model based on the Maxwell-Wagner effect, portrayed in Figure 1b, the plateau region representing the saturated potential should appear after reaching the SH intensity maximum when s MW >> s RC [34].…”
Section: Resultssupporting
confidence: 70%
“…Upon application of the external voltage, SH intensity increases from baseline level (at V ex = 0) until it reaches its maximum value at around 10 À7 s, the increase corresponding to charging of electrodes. The response time of the charging process agrees well with the calculated value for the equivalent circuit, s RC = R s C⁄ % 4 Â 10 À8 s. Smooth carrier injection follows, with holes being transported and accumulated at the pentacene/polyterpenol interface, as reflected by the rapid decrease in SH intensity commencing at $5 Â 10 À6 s to its initial baseline level, which it reaches at approximately 10 À5 s. Similar carrier injection behaviour has been reported for comparable pentacene-based device with polyimide blocking layer, where SH intensity was demonstrated to relax to the zero level at approximately 10 À3 s under forward bias charging conditions [36]. According to the equivalent circuit model based on the Maxwell-Wagner effect, portrayed in Figure 1b, the plateau region representing the saturated potential should appear after reaching the SH intensity maximum when s MW >> s RC [34].…”
Section: Resultssupporting
confidence: 70%
“…Finally, SH light was detected by a monochromator synchronized with the laser source, in the same manner as in our previous study. 6 Keeping in view the absorption and PL spectra of the material, the fundamental laser wavelength was scanned in the range of 800-1100 nm. By impinging the selective laser wavelengths on the BHJ layer, the EFISHG signals in PCDTBT and PC 71 BM are generated due to the coupling of electrons in the molecules and electromagnetic wavesẼðxÞ.…”
Section: B Efishg Measurementmentioning
confidence: 99%
“…Nevertheless, using buffer layers such as PEDOT:PSS significantly improves OSC performances. 6,7 This motivated us to study the impact of the use of PEDOT:PSS buffer layer on the internal electric field in the BHJ layer, and to study the carrier transport in the PCDTBT:PC 71 BM bulk heterojunction organic solar cells. Finally, we found that TR-EFISHG is a novel way of probing the carrier transport in bulk-hetero structure OSCs, and thus can be used for studying the impact of interfacial layer on electron and hole transport in bulk-heterojunction OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we employed the Maxwell-Wagner (MW) model analysis for studying interfacial phenomena in double-layer organic devices, e.g., double-layer organic light-emitting diode (OLED) and showed the potentiality of this analysis based on a dielectrics physics approach. [7][8][9] These results motivated us to apply the MW model to analyze carrier generation and transport processes in OSCs.…”
mentioning
confidence: 97%
“…Consequently, we are paying attention to electric-field-induced secondharmonic generation (EFISHG) measurement, which is available for directly probing the electric field distribution in organic devices in terms of carrier behaviors. 9,13,14 The EFISHG measurement coupled with IS measurement provides a clear understanding of interfacial phenomena related to the photovoltaic effect in OSCs.…”
mentioning
confidence: 99%